A pot of gold at the end of the rainbow? A spectrum of attitudes to assisted reproductive technologies in Ireland. (1st January 2018) - Dempsey, Maria; King, Rob; Nagy, Andrea
Abstract: Objective: New technologies present new ethical dilemmas. Our ethical intuitions may mislead us in relation to new technologies such as nuclear power, vaccines, GMOs and assistive reproductive technologies (ART). Between 1999 and 2008 the number of ART treatment cycles increased by 265% in Ireland. The implications and potentials of such technologies are profound – challenging existing understanding of humans' relationships to reproduction. Because such technologies are comparatively unregulated, and their use has only been occurring for a single generation, detailed investigation of how awareness of ART influences understanding of personal fertility is needed.Method: Data from a general Irish population of varied ages and both sexes ( N  = 611) were collected through an online survey which included demographics, knowledge of fertility, knowledge of ART and personal fertility.Results: Latent class analysis revealed a typology of five groups of responders to ART distinguished by their attitudes and knowledge of this technology. These groups are labelled as 'Worried Yet Willing', 'Live and Let Live', 'Disengaged', 'Judgemental' and 'Conflicted'.Conclusion: Responses to the introduction of ART in Ireland fall into at least five distinct groups. Understanding of the distinguishing features of these types of responders is important for fertility healthcare professionals in terms of service development and delivery. Implications for the direction of future related research is discussed.